STATISTICAL OBSERVATION: CONTENT, IMPORTANCE AND DIRECTIONS FOR DEVELOPMENT - Gulomova Musharrafkhan Rafiqjon qizi (Ecomind Press, 2025)
The article examines the essence of statistical observation as a fundamental category of modern statistics. Its content, structure, and role in ensuring the accuracy and completeness of information required for managerial decision-making are revealed. Particular attention is paid to the importance of statistical observation in macroeconomic development, social policy, demography, healthcare, education, and market analysis. It is emphasized that the effectiveness of the statistical system depends on the quality of the organizational and legal framework, the level of digitalization, and public trust in statistical data. The paper also outlines the main directions for the development of statistical observation: the implementation of international standards, the use of modern technologies (big data, artificial intelligence), increasing transparency and accessibility of data, as well as strengthening the institutional independence of statistical agencies.